Obturation Technique Used for Open Apex Management - A Retrospective Analysis - Bianca Princeton , Dr. Adimulapu Hima Sandeep, (South Eastern European Journal of Public Health, 2025)
Introduction: Obturation technique is a method of filling of internal resorption and sealing a cleaned, shaped root canal using a root canal sealer with core filling material. Apexification and apexogenesis are two endodontic procedures that attempt to induce apical repair. The techniques employed for obturation for open apex includes warm vertical condensation, thermoplasticized injection technique, lateral condensation, and roll cone technique. The aim of this retrospective study is to analyze and assess the obturation technique employed for the management of open apex. Materials & Method: The present study involved obtaining the records of 40 different patients from an electronic database of Saveetha dental college. The different obturation techniques undergone by the patients for non vital open apex management was recorded and documented. Results: It was demonstrated that out of 40 dental patients, 25 of them had undergone lateral compaction obturation technique and 9 matched taper single cone technique. About 9 patients out of 40 had been subjected to rolled cone and warm vertical condensation techniques. The Pearson chi-square test indicated that p value was 0.008 (<0.05), which was proven to be statistically significant. Conclusion: Within the limitations of the study, the obturation technique utilized for open apex management was analyzed and it was perceived that most of the patients had been subjected to lateral condensation obturation technique.